2013
DOI: 10.3189/2013aog62a161
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale spatial variability of lidar-derived and modeled snow depth on Hardangervidda, Norway

Abstract: This study presents results from an Airborne Laser Scanning (ALS) mapping survey of snow depth on the mountain plateau Hardangervidda, Norway, in 2008 and 2009 at the approximate time of maximum snow accumulation during the winter. The spatial extent of the survey area is >240 km2. Large variability is found for snow depth at a local scale (2 m2), and similar spatial patterns in accumulation are found between 2008 and 2009. The local snow-depth measurements were aggregated by averaging to produce new datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 46 publications
3
52
1
Order By: Relevance
“…Our hypothesis is motivated by the observation of Liston et al (1999), in that, in contrast to summer convective-precipitation systems, the spatial distribution of winter precipitation is more influenced by topographic distributions. Furthermore, it is motivated by the results of Grünewald et al (2013) and Melvold and Skaugen (2013), which confirmed that the snow depth distribution is dominated by topography at scales of several hundred meters.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our hypothesis is motivated by the observation of Liston et al (1999), in that, in contrast to summer convective-precipitation systems, the spatial distribution of winter precipitation is more influenced by topographic distributions. Furthermore, it is motivated by the results of Grünewald et al (2013) and Melvold and Skaugen (2013), which confirmed that the snow depth distribution is dominated by topography at scales of several hundred meters.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, Grünewald et al (2013) and Melvold and Skaugen (2013) therefore investigated the influence of scale on aggregated snow depth data. By analyzing snow depth data in differently sized grid cells up to 800 m for several catchments, Grünewald et al (2013) found a lower limit of 400 m for the grid cell size to explain most of the remaining larger-scale spatial variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne laser scanning (ALS) from helicopters or airplanes can cover larger areas in a shorter time also under difficult avalanche danger situations. Recent studies demonstrate that the accurate mapping of snow depth is possible (Deems et al, 2013;Melvold and Skaugen, 2013). However, the costs to cover larger areas are still high and overflights are, as with digital photogrammetry, restricted to fair weather conditions.…”
Section: Y Bühler Et Al: Snow Depth Mapping In High-alpine Catchmentsmentioning
confidence: 99%
“…The advantages of lidar for spatially characterizing snow depths over large remote areas are finally being used to assess lower-resolution operational hydro-meteorologic snow models. Melvold and Skaugen (2013) used six parallel 500 m × 80 km lidar surveys, each separated by 10 km, to investigate the Norwegian operational temperature index snow model, seNorge. After upscaling the lidar-derived 2 m resolution snow depths to the spatial resolution of the 1 km 2 gridded model output, the modeled results were found to accurately represent the remote sensing estimates despite the lack of sub-grid spatial information within the model structure.…”
Section: A Hedrick Et Al: Lidar Validation Of Snodasmentioning
confidence: 99%